Plasmid Replicons from Pseudomonas Are Natural Chimeras of Functional, Exchangeable Modules - Bardaji, Leire; Añorga, Maite; Ruiz-Masó, José A.; del Solar, Gloria; Murillo, Jesús (Frontiers in Microbiology, 2017)
Plasmids are a main factor for the evolution of bacteria through horizontal gene exchange, including the dissemination of pathogenicity genes, resistance to antibiotics and degradation of pollutants. Their capacity to duplicate is dependent on their replication determinants (replicon), which also define their bacterial host range and the inability to coexist with related replicons. We characterize a second replicon from the virulence plasmid pPsv48C, from Pseudomonas syringae pv. savastanoi, which appears to be a natural chimera between the gene encoding a newly described replication protein and a putative replication control region present in the widespread family of PFP virulence plasmids. We present extensive evidence of this type of chimerism in structurally similar replicons from species of Pseudomonas, including environmental bacteria as well as plant, animal and human pathogens. We establish that these replicons consist of two functional modules corresponding to putative control (REx-C module) and replication (REx-R module) regions. These modules are functionally separable, do not show specificity for each other, and are dynamically exchanged among replicons of four distinct plasmid families. Only the REx-C module displays strong incompatibility, which is overcome by a few nucleotide changes clustered in a stem-and-loop structure of a putative antisense RNA. Additionally, a REx-C module from pPsv48C conferred replication ability to a non-replicative chromosomal DNA region containing features associated to replicons. Thus, the organization of plasmid replicons as independent and exchangeable functional modules is likely facilitating rapid replicon evolution, fostering their diversification and survival, besides allowing the potential co-option of appropriate genes into novel replicons and the artificial construction of new replicon specificities.